Penguatan Literasi, Kesehatan, dan Lingkungan melalui Program Kuliah Kerja Nyata di Desa Pagedangan Ilir - Ayi Krisna Widya Adhi Nugraha; Dian Restu Indrayanti; Nana Permana; Prama Agam Handoyo; Supriyandi Supriyandi; Halimatus Sya Diah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Community Service Program (Kuliah Kerja Nyata – KKN) in Pagedangan Ilir Village was implemented to strengthen community awareness of the importance of literacy, health, and environmental preservation. The program was initiated in response to low reading interest, unhealthy lifestyles, and suboptimal waste management practices in the community. The methods employed included community education through counseling, training, and participatory diffusion of science and technology. The results showed a 45% increase in community understanding of family literacy, a 38% improvement in clean and healthy living behavior (PHBS), and a 52% enhancement in household waste management. This activity had a positive impact on social awareness and the overall quality of life of the villagers.